Hydrogen sorption properties of some RM2-xM'x and RM2-xAlx (R = Y, Gd, Tb, Er, Ho; M = Mn, Fe, Co, Ni) Laves phase ternary compounds - Kotur, Bogdan Jaroslavovič (Array, 2009)
Summary: A literature and authors' review of influence of hydrogen absorption on the crystal structure of binary RM2 and ternary RM2-xM'x, R1-xR'xNi2 and RM2-xAlx (R = Rare earth; M = Mn, Fe, Co, Ni) Laves phase compounds are presented. Majority of these compounds absorb hydrogen at pressure 0.1–0.12 MPa and room temperature preserving the crystalline state. The phases form hydrides with the amount of hydrogen up to 4.2 atoms H per formula unit (at.H/f.u.) and up to 5 at.H/f.u. at high hydrogen pressure. The unit cell volume increases under hydrogenation up to 20 % and up to 30 % at high hydrogen pressure. In many cases the doping of binary phases by the third element increases hydrogenation capacity of intermetallics under the same hydrogenation conditions. The structure of the parent compound is preserved or slightly distorted during hydrogenation